The selection of public transportation modes in industrial era 4.0 - Faizal Haris Eko Prabowo; Endang Rustendi; Annisa Nurbaiti (Faculty of Economics and Business Mulawarman University, 2020)
Industrial Revolution 4.0 opens opportunities as well as challenges for an industry, the opportunity is to develop market share to be broader with the internet while the challenges are conventional methods that need to be changed to become easier because of the needs of consumers to keep up with the times. These changes have an impact on the economic field, especially business. Not only globally, Indonesia also experienced a lifestyle change in consuming products and services that are currently not free from the use of internet platforms. Transportation services are currently one of the industries that are undergoing rapid changes. The reduced interest of passengers using conventional transportation has caused transportation modes to lose the market share that they have had for a long time, which also has an impact on the sales they get. The purpose of this study is to analyze the decision to use public transportation modes by millennial generation passengers. This study used a survey method and case study design with a qualitative approach. The population and sample in this study are consumers using public transport services aged 18-37 years or millennial generations. The results of this study explain that millennial passengers prefer online transportation modes than conventional transportation modes. If conventional transportation wants to remain competitive in this industry, they are likely to need to cooperate with the private sector as well as the government as a regulator by making rival applications as a competitive advantage.